Competition, reach for yield, and money market funds - La Spada, Gabriele (Journal of Financial Economics, 2018)
Do asset managers reach for yield because of competitive pressures in a low rate environment? I propose a tournament model of money market funds (MMFs) to study this question. When funds care about relative performance, an increase in the risk premium leads funds with lower default costs to increase risk taking, while funds with higher default costs decrease risk taking. Without changes in the premium, lower risk-free rates reduce the risk taking of all funds. I show that these predictions are consistent with MMF risk taking during the 2002–2008 period and that rank-based performance is a key determinant of money flows to MMFs.